Carcinoembryonic antigen and recurrence in survival of patients with resection of colorectal cancer - Cribilleros Barrenechea, Jorge Renato (2014)
Introduction: Carcinoembryonic antigen (CEA) has been associated with advanced stage, poor survival and early detection of recurrent colorectal cancer (CRC). Objectives: To determine relation between serum CEA and recurrence and survival of patients with curative resection of colorectal cancer. Design: Retrospective, correlational and explanatory study. Setting: Department of General and Oncology Surgery, Service of Colon and Rectum, Hospital Nacional Rebagliati Martins, EsSalud, Lima, Peru. Participants: Patients with curative resection of CRC. Methods: Patients with curative resection of CRC at Rebagliati Hospital during years 2000-2003 were followed until 2010. For variables quantitative comparison T test mean differences was used, and Kaplan-Meier method and Cox regression survival analysis techniques were used. Main outcome measures: Patients recurrence and survival. Results: Increased serum CEA in the pre and postoperative periods was related to significant increased recurrence of colorectal cancer (p <0.05). Survival in patients with pathological CEA was significantly lower than in patients with standard CEA (p <0.05). Conclusions: Elevated serum carcinoembryonic antigen was related to increased colorectal cancer recurrence. Serum CEA values in the preoperative period would be predictive of survival.